"The possible implication of endothelin in the pathology of COVID-19-induced pulmonary hypertension". (December 2021) - Nabeh, Omnia Azmy; Matter, Lamiaa Mohammed; Khattab, Mahmoud Ahmed; Esraa Menshawey,
Abstract: COVID-19 pandemic has changed the world dramatically since was first reported in Wuhan city, China [1]. Not only as a respiratory illness that could lead to fatal respiratory failure, but also some evidences suggest that it can propagate as a chronic disease associated with a variety of persistent post COVID-19 pathologies that affect patients' life [2, 3]. Pulmonary hypertension (PH) is one of the challenging diseases that may develop as a consequence of SARS-COV-2 infection in some COVID-19 survivors [4, 5]. The vasopressor, proliferative, proinflammatory, and prothrombotic actions of endothelin [6] may be encountered in the COVID-19-induced PH pathology. And so, endothelin blockers may have an important role to restrict the development of serious PH outcomes with special precautions considering patients with significant hypoxemia.